Prediction of rowing performance from anthropometric and metabolic variables in lightweight and heavyweight male rowers - Mäestu, J. (University of Tartu, Faculty of Exercise and Sport Sciences Institute of Sport Pedagogy, 2001)
A typical rowing competition takes place over a 2000 metre course and lasts about 6 - 7 minutes depending on the boat type. A rower has to perform about 250 strokes during this time. Rowing demands a high level of strength and endurance. A large body mass is involved in rowing and body size and body mass are undoubtedly performance related factors (Shephard 1998; Steinacker 1993). Rowing is divided into two categories - sculling (rowers use two oars) and sweep (rowers use one oar) rowing. Differences in anthropometric and metabolic characteristics have been observed between those groups. Rowing competitors are also divided in two categories - lightweight and heavyweight rowers. In lightweight rowing, the maximal body mass of a male rower may reach 72.5 kg and the average of a crew 70.0 kg in male rowers. The performance of a crew can be measured by their 2000 metre rowing race time. However, it is very difficult to assess physiological parameters during on-water rowing, because of the possible wind and current (Jensen 1994; Shephard 1998). Graven et al. (1993) analysed the rowing stroke on a Concept II (Morrisville, USA) rowing ergometer and concluded that it provides a close approximation to the movements of the rowing stroke and allowes accurate measurements of the physiological changes produced during rowing. Although rowing on an ergometer does not require the same skills as on-water rowing, it has been observed that the ergometer simulates the biomechanical and metabolic demands of on-water rowing (Lamb 1989; Mahony et al. 1999; Rodriguez et al. 1990). Therefore, rowing ergometers are commonly used to measure individual physiological performance variables and training changes (Bouckaert et al. 1983; Hahn et al. 1988). The 2000 metre time trial on a rowing ergometer has widely been used to assess rowing performance (Cosgrove et al. 1999; Russell et al. 1998; Womack et al. 1996). However, research has demonstrated that 2000 metre rowing ergometer race is significantly faster, and therefore more intensive than 2000 metre on-water rowing race (Jürimäe et al. 1999b). Accordingly, 2000 metre rowing ergometer time trial may not exaclty reflect the metabolic effort of on-water rowing. 2500 metre time trial on a rowing ergometer has been used to assess rowing performance (Kramer et al. 1994; Messonnier et al. 1997). In this experiment, a 2500 metre rowing ergometer race was used to assess rowing performance in male lightweight and heavyweight sculling rowers. The development of models based on laboratory data, by which performance in everyday skills can be predicted, is of enduring intrest and has practical importance for talent identification and for the development and assessment of activity-specific training programmes. In addition, performance prediction modelling has a contribution to make to understanding the physiological characteristics of a given activity (Russell et al. 1998). Performancce prediction models have successfully been developed for running (Morgan et al. 1989), cycling (Craig et al. 1993) and junior sweep rowing (Russell et al. 1998). To our knowledge, no studies have carried out to develop performance prediction models for lightweight and heavyweight sculling rowers. In this experiment performance prediction models were developed for male lightweight and heavyweight sculling rowers using different anthropometric and metabolic variables.